Repeated assessment of key clinical walking measures can induce confounding practice effects. (October 2020) - Meyer, Christian; Killeen, Tim; Lörincz, Lilla; Curt, Armin; Bolliger, Marc; Linnebank, Michael; Zörner, Björn; Filli, Linard
Accurate functional outcome measures are critical for both clinical trials and routine patient assessments. Many functional outcomes improve with test repetition, a phenomenon that can confound the findings of longitudinal assessments. In this viewpoint, we tackle the poorly considered issue of practice effects in prevailing clinical walking tests based on current literature, while also presenting the original data from our own work, in which we investigated practice effects in the timed 25-foot walk (T25FW), timed-up and go (TUG), and 2-minute walk test (2MWT). In these tests, performed on 3 consecutive days in 10 patients with multiple sclerosis and 40 healthy controls, we observed significant practice effects in several established walking outcomes, including a 9.0% improvement in patients' TUG performance ( p = 0.0146). Pre-training in these walking tests prior to baseline measurement may mitigate practice effects, thereby improving the accuracy and value of their repeated use in research and clinical settings.